2008
DOI: 10.1037/a0013720
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved anger and sadness: Identifying vocal acoustical correlates.

Abstract: The authors conducted 2 studies to identify the vocal acoustical correlates of unresolved anger and sadness among women reporting unresolved anger toward an attachment figure. In Study 1, participants (N = 17) were induced to experience and express anger then sadness or sadness then anger. In Study 2, a 2nd group of participants (N = 22) underwent a relationship-oriented, emotion-focused analogue therapy session. Results from both studies showed that, relative to emotionally neutral speech, anger evoked an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 43 publications
(46 reference statements)
0
36
0
Order By: Relevance
“…Accordingly, inspection of the Rochman et al study [45] reveals an articulation rate of 190.09 WPM, which compares to a value of 191.30 WPM (SD=29.44) in Group I in the present study. Similarly, in the Diamond et al study [46], a speaking rate of 5.90 SPS was reported, which compares to a value of 5.97 SPS (SD=0.75) in Group I in the present study.…”
Section: Current Versus Previous Results In Hebrewmentioning
confidence: 81%
See 1 more Smart Citation
“…Accordingly, inspection of the Rochman et al study [45] reveals an articulation rate of 190.09 WPM, which compares to a value of 191.30 WPM (SD=29.44) in Group I in the present study. Similarly, in the Diamond et al study [46], a speaking rate of 5.90 SPS was reported, which compares to a value of 5.97 SPS (SD=0.75) in Group I in the present study.…”
Section: Current Versus Previous Results In Hebrewmentioning
confidence: 81%
“…The only other two studies that reported partial data on articulation-and speaking-rate among Hebrew speakers have examined young women (age range 22-24 years, and 21-26 years) during conversations made under elicited emotional conditions, compared to conversations made during a neutral emotional condition [45,46]. Hence, comparison of these studies enables the evaluation of the measurements taken during the neutral emotional condition, in conjunction with the values obtained from Group I (the younger group) in our study.…”
Section: Current Versus Previous Results In Hebrewmentioning
confidence: 99%
“…The majority of this research has focused on fundamental frequency; however, increases in pitch and pitch fluctuations have been observed in individuals when speaking under stressful situations [28, 33, 34]. AWS’ significant increases in FFF2 compared to ANS’ when speaking under arousing conditions reflected a decreased ability to maintain a steady-state posture for vocal tract musculature when under emotional influences.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral studies assessing speech – motor control in response to anxiety – have documented increases in errors and disfluencies when speaking under emotionally arousing conditions, such as when giving a speech [28]. Studies assessing the acoustic properties of speech have shown higher pitch and loudness levels [29-34] as well as greater pitch fluctuations [28, 35] when experiencing heightened emotions along a variety of domains including happiness, sadness, and anxiety. Studies assessing articulatory control in relation to emotion are not as prevalent, most likely because the techniques used such as ultrasound [36] and magnetic resonance imaging [37] are not as conducive to eliciting natural emotional expression in the laboratory setting.…”
Section: Introductionmentioning
confidence: 99%
“…Several neurophysiological studies of adult attachment assessing the autonomic nervous system, the hypothalamic-pituitary-adrenocortical axis or frontal electroencephalography (EEG) asymmetry used self-report measures (Carpenter and Kirkpatrick, 1996; Kim, 2006; Laurent and Powers, 2007; Rochman et al, 2008; Zhang et al, 2008; Kiss et al, 2011; Dan and Raz, 2012), while other studies used narrative interview measures of attachment such as the Adult Attachment Interview (AAI) and the Adult Attachment Projective Picture System (AAP; Beijersbergen et al, 2008; Buchheim et al, 2009; Fraedrich et al, 2010; Holland and Roisman, 2010; Behrens et al, 2011; Leyh et al, 2016). …”
Section: Introductionmentioning
confidence: 99%